CREATION OF AN AUTONOMOUS LEARNING MODEL TO IMPROVE THE LEARNING OUTCOMES OF PHYSICS FOR HIGH SCHOOL STUDENTS - Jon Darmawan; Abdul Hasan Saragih; Ridwan Abdullah Sani; Putri Mayasari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Abtract